Application of rapid evaporative ionization mass spectrometry in preclinical and clinical analyses of steatotic liver tissues and cells - Julian Connor Eckel; Lena Seidemann; Mohamed Albadry; Gerda Schicht; Marija Skvoznikova; Sandra Nickel; René Hänsel; Daniel Seehofer; Grit Gesine Ruth Hiller; Hans-Michael Tautenhahn; Uta Dahmen; Georg Damm (Scientific Reports)
Abstract Rapid evaporative ionization mass spectrometry (REIMS) shows promise as a preparation-free tissue analysis tool with the prospect for real-time diagnostics. Given that hepatic steatosis is characterized by shifts in lipid species and abundance, we selected it as basis for method development, as REIMS specifically measures lipidomic profiles. However, further validation and protocol refinement are necessary to establish its clinical utility. In this study, we applied REIMS to steatotic human liver tissues, focusing on its ability to differentiate varying degrees of steatosis. We established standardized protocols for tissue handling and lipid analysis, which were essential for reliable data interpretation. Notably, our findings revealed that tissue size impacts REIMS sensitivity, with smaller samples yielding lower total ion counts and altered lipid profiles. Through principal component analysis, we identified key lipid classes, namely triacylglycerides, fatty acids, and glycerophospholipids. Despite a missing link between triacylglyceride abundance and degree of steatosis, we successfully identified condition-specific lipid patterns, with ceramides emerging as markers of advanced steatosis. Our study provides a protocol for the measurements of lipid standards showing the detailed degradation of specific lipids using iKnife-coupled REIMS. It highlights the pitfalls and limitations and provides critical recommendations for REIMS use. It also emphasizes the need for standardized biobanking and tissue preparation to ensure accurate lipid profiling, laying the groundwork for future protocol adjustments required for clinical application.